Pengaruh Dakwah Terhadap Kepatuhan Hukum Islam Di Kalangan Mahasiswa Universita Islam Negeri Sumatera Utara - Arini Dwi Utari; Alya Artika Nasution; Destry Diah Loka; Naimatul Akmil Daulay (Tabayyun : Journal Of Islamic Studies, 2025)
This study aims to analyze the impact of da'wah on the level of compliance with Islamic law among students at the State Islamic University of North Sumatra (UINSU) using a qualitative approach. The method employed is a phenomenological study, where data was collected through in-depth interviews, observation, and documentation from students across various faculties. The results show that da'wah delivered through lectures, regular study sessions, and social media has a significant influence on shaping students' understanding and adherence to Islamic law, particularly in the aspects of worship, mu'amalah, and ethics. The findings indicate that students consistently exposed to da'wah exhibit higher levels of compliance compared to those who are minimally involved in da'wah activities. This study concludes that da'wah plays a crucial role as an instrument to strengthen the implementation of Islamic law among students, with recommendations to optimize da'wah approaches based on dialogue and digital technology.